The New Theories on Business Judicial Reorganization in the Brazilian System - Carnio Costa, Daniel (International Journal of Insolvency Law, 2017)
[extract] The Brazilian Legislation on bankruptcy is inspired on the US Bankruptcy Code when it comes to business reorganization. It is important to note, however, that the legislations are not the same, but the Brazilian legislators have looked to the same principles of the Chapter 11 of the US Bankruptcy Code to build the Brazilian Business Reorganization in 2005, in order to create in a similar way some important institutes like the stay period, the plan of reorganization and the creditors meeting, among others. A general overview of the insolvency systems around the world shows us that before the US Bankruptcy Code of 1978 with the amendments of 1984 and 2005 there were only two insolvency models: creditor oriented legislations and debtor oriented legislations.